Effect of inter-personal communication on cervical cancer knowledge and prevention among women in Rural Bengaluru, India - Garima Kumari; H R Raveendra Reddy; Nivedita B M (Journal of Current Oncology and Medical Sciences)
Introduction: Cervical cancer is one of the leading causes of cancer among women worldwide. In 2012, 528,000 new cases of cervical cancer were diagnosed globally, 85% of which were in less developed countries of Sub-Saharan Africa, Asia (including India) and Central and South American countries. Currently, cervical cancer is the 2nd leading cause of cancer deaths in India which approximately accounts to 1/3rd of the global cervical cancer deaths. High-risk types are HPV16 & 18 and they account for more than 90% of cervical carcinoma and the route of transmission is mainly by sexual contact, which can be prevented by health education. The present study was conducted among rural reproductive women where the prevalence of cervical cancer is high and can be prevented by using a simple intervention method of health education.